LINGKUNGAN DAN INTENSI BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI - Fernando Saragih; Asep Munawar; Erika Feronika Br Simanungkalit; Jesika Artha Theresia Sihotang (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2022)
Entrepreneurial intention is a realistic picture of the community's desire to establish and develop a business or business. This variable is strongly influenced by many different factors and situations, especially during the Covid-19 pandemic. With this level of influence, researchers are interested in studying and analyzing how environmental variables can affect business intentions. The approach used in this research is quantitative (ex post facto method) with multiple regression analysis (SPSS 20). Environmental variables focus on 2 independent variables (peer environment and home environment) which are represented by 28 statements. while the fixed variable is represented by 14 statements. In addition, to fulfill the research requirements and multiple regression, the researcher also conducted an instrumental test and a classical hypothesis test so that this research can be declared feasible. Based on the analyzed data and procedures, the results obtained that the home environment has a positive and significant effect, but this is different from the peer environment variable which has a negative effect.